Host glycolipids in SARS-CoV-2 entry - Uraki, Ryuta; Kawaoka, Yoshihiro (Nature chemical biology, 2022)
A new study demonstrates that the receptor-binding domain of the SARS-CoV-2 spike protein binds to sialylated glycans, especially glycolipids, to facilitate viral entry, an insight that identifies new potential targets for SARS-CoV-2 interventions.